Quantifying technical load and physical activity in professional soccer players during pre-season matches with IMU technology - Losada-Benitez, José Augusto; Nuñez-Sánchez, Francisco Javier; Barbero-Álvarez, José Carlos (Frontiers in Physiology, 2023)
This study aimed to record, analyze and quantify professional soccer players' technical (TL) and physical load (PL) in friendly matches to compare their records during the first and second halves and between players with different positions. Eighteen professional soccer players, 24.6 ± 2.7 years, 1.78 ± 0.3 height (m), 74.6 ± 4.5 body mass (kg), 9.8 ± 2.2 body fat (%), and 65.6 ± 2.7 maximal oxygen consumption (VO 2max , ml•kg -1 •min -1 ) were monitored during six preseason friendly matches to analyze the activity profile using technical and physical variables through inertial measurement unit (IMU). No significant differences were found between the periods for the TL and PL. Significant differences were found between specific positions: Full Back (FB: n=4), Central Defender (CD: n=3), Midfielder (MD: n=4), Winger (WG: n=4), and Forward (FW: n=3), both the TL and PL. We conclude that the PL profile based on his playing position is independent of the development of the PL shown during friendly matches. The monitoring, quantifying, and controlling of the TL added to the PL provides a more holistic vision of soccer players in friendly matches. The relative ease IMU application technology offers an alternative with less time-cost and more significant benefits than other types of technologies applied up to now.